Cauca leads climate smartness for agriculture in Colombia reaching 150,000 farmers - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
In 2017, CCAFS, Ecohabitats Foundation and rural communities collaborated to promote the Climate-Smart Villages (CSVs) in Cauca, Colombia. This led to an investment of USD 66 million from the Royalties National Fund to scale climate-smart agriculture (CSA) in at least 8 municipalities.